Sensory Profiling of Milkfish Otak-Otak from Gresik Regency with the Rate-All-That-Apply Method - Dwiyanti, Nabilla Nova; Winarti, Sri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The community widely consumes milkfish otak-otak, a traditional food product from Gresik. It is produced by various small and medium enterprises (SMEs), resulting in diverse sensory characteristics across products. This study aimed to assess the taste and smell characteristics of milkfish otak-otak from five small and medium-sized enterprises (SMEs) in Gresik The results revealed that each sample displayed distinctive sensory attributes. Samples B1 and B2 were characterized by orange, brown, and red colors, with smoky aroma, bitter taste, and oily mouthfeel. Sample B3 was associated with sweet, coconut, and fishy aromas, along with sour and sweet tastes, and a dense and chewy texture. Sample B4 was identified by its yellow color, distinctive milkfish flavor, fibrous texture, dry mouthfeel, and throat irritation. In contrast, Sample B5 exhibited dominant attributes such as salty and savory tastes, herbs and spices flavor, spicy and seasoned aromas, spicy mouthfeel, and a soft texture. Preference mapping analysis indicated that Sample B5 had the highest liking score of 75%, driven by the preferred attributes of salty and savory taste, herbs and spice flavor, and seasoning aroma. These findings provide valuable insights for SMEs in improving the formulation and processing of milkfish otak-otak to better match consumer preferences.Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 8: Decent Work and Economic Growth